2018
DOI: 10.1111/1759-7714.12588
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of diagnostic procedures, genetic aberration analysis, and first‐line treatment of lung cancer in Jiangsu Province, China

Abstract: BackgroundJiangsu Province, China, is highly developed economically and culturally, and has a high prevalence of lung cancer. We aimed to evaluate the diagnostic procedures, genetic aberration analysis status, and first‐line treatment models of lung cancer in Jiangsu Province.MethodsLung cancer patients diagnosed in 2016 at 22 tertiary care hospitals were evaluated. Demographic characteristics, tumor histology, staging, family history of lung cancer, auxiliary examinations, genetic testing, and first‐line trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Gene mutations play an important role in the tumorigenesis and progress of lung adenocarcinoma and provide ideas for targeted treatment in lung cancer. 26 To further explore the important biological function of CXC chemokines in LUAD, we used GO enrichment analysis and KEGG pathway enrichment analysis to examine the biological behavior of differentially expressed CXC chemokines. Interestingly, we found that these genes were mainly involved in biological processes, including cytokine-cytokine interaction, chemokine signaling pathway, and IL-17 signaling pathway.…”
mentioning
confidence: 99%
“…Gene mutations play an important role in the tumorigenesis and progress of lung adenocarcinoma and provide ideas for targeted treatment in lung cancer. 26 To further explore the important biological function of CXC chemokines in LUAD, we used GO enrichment analysis and KEGG pathway enrichment analysis to examine the biological behavior of differentially expressed CXC chemokines. Interestingly, we found that these genes were mainly involved in biological processes, including cytokine-cytokine interaction, chemokine signaling pathway, and IL-17 signaling pathway.…”
mentioning
confidence: 99%